Physical Examination of Patients from a Glaucoma Perspective - Masood Alam Shah, Amjad Akram (Pakistan Journal of Ophthalmology, 2012)
Many years ago one of our teachers in Ophthalmology said to us during a clinical tutorial:”It is very easy to forget that the eyes are attached to a structure called ’the Body’, diseases of which can affect the eyes”. He was actually highlighting the fact that a very significant number of ophthalmologists develop ‘tubular vision’ concentrating only on the eyes of a patient and not considering patient as a whole. Advantages in carrying out a systemic assessment of patients are many and include: (1) Diagnosis, particularly with an atypical presentation (2) General management plan (3) Surgical decisions